KARAKTERISTIK MADU LEBAH HUTAN (Apis dorsata Fabr.) DARI BERBAGAI BIOREGION DI RIAU - Avry Pribadi; M. Enggar Wiratmoko (Jurnal Penelitian Hasil Hutan, 2019)
Characteristics of Apis dorsata`s forest honey from bioregions of Riau have not been studied intensively. Thisresearch is aiming to provide characteristic information on honey from bioregions of Riau based on SNI 8664-2018.The study was conducted in September to November 2015. Honey samples were collected from eight districts of sixbioregions in Riau Province, i.e Bengkalis and Selat Panjang (downstream), Kampar (mineral forest), Pelalawan(peat swamp forest), Rokan Hilir (river bank), Siak (Acacia plantation forest), and Kuansing (oil palm and rubberplantation). Samples of each bioregion were analyzed based on SNI 8664-2018 procedures. Results show that wildhoney characteristics were not significantly different among bioregions for almost all parameters in SNI 8664-2018.However, the diastase enzyme parameter in honey taken from Pelalawan was the only parameter that had significantvalue. In addition, the parameter of water content and reducing sugar content were only two parameters that did notmeet the SNI 8664-2018 requirements. Meanwhile, the type and size of pollen could be used for determining the originof honey between Riau bioregions.